Supporting online students : a guide to planning, implementing, and evaluating services - Crawley, Anita, 1946- (San Francisco, CA : Jossey-Bass, 2012)
"Online Student Services and Support is a comprehensive review of all aspects of support services needed by online learners. It argues that while these services are necessary for online students to be successful, they will benefit all students. Based on a decade's worth of published research, it describes the scope of services that should be made available to online students in three separate stages of their college careers. It offers guidelines and standards for these services as outlined by half a dozen national professional organizations; covers the nationally used audit tool developed by the Center for the Transforming Student Services (CENTSS)"--
Includes bibliographical references and index.
Keywords: Web-based instruction; Students -- Services for -- Technological innovations